1966
DOI: 10.1111/j.1600-0765.1966.tb01869.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal health in various ethnic groups in Israel

Abstract: The periodontal status of approximately 5,000 subjects belonging to nine ethnic groups of Oriental origin, aged four years and above and living in villages in Israel, was investigated. The severity of periodontal involvement of a group was found to be similar whether expressed as gingivitis in childhood or as destructive periodontal disease in adolescence and adult life. Gingivitis reached its peak at the age of 10 to 11 years and then tended to level off or even decline. The periodontal index (PI) and gingiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…This study revealed that Khat chewers had significantly more attachment loss and more gingival recession than non-chewers, which is in agreement with most of previous studies (5,8,12,13,17). A plausible explanation of these findings is that chronic and intense khat chewing probably results in chronic trauma and vertical impaction to the periodontium, resulting in gingival recession and attachment loss.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study revealed that Khat chewers had significantly more attachment loss and more gingival recession than non-chewers, which is in agreement with most of previous studies (5,8,12,13,17). A plausible explanation of these findings is that chronic and intense khat chewing probably results in chronic trauma and vertical impaction to the periodontium, resulting in gingival recession and attachment loss.…”
Section: Discussionsupporting
confidence: 92%
“…While most studies found a positive association between khat chewing and the occurrence of periodontal diseases (5,8,10,12-14), some did not report this association (15,16). Rosenzweig and Smith (17) were the first investigators to suggest a possible effect of khat chewing on periodontal tissues. In their study, the authors found that Yemeni Jews had higher rates of periodontal diseases compared to other ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco smoking can affect periodontal tissues directly, causing local irritation, and gingival pockets tend to be greater in the maxillary lingual sites (27). However, the difference was reversed in the 35–44‐ and 45–54‐years age groups, whereby the nonsmokers appeared to have significantly higher mean upper tooth loss compared with smokers, a situation that may be ascribed to inferior oral hygiene status because oral care is given low priority, or even neglected altogether, by those within these age groups in Yemen (28).…”
Section: Discussionmentioning
confidence: 99%
“…The association between khat use and periodontal diseases (Rosenzweig and Smith, 1966), stomatitis, and teeth staining (Halbach, 1972;Luqman and Danowski, 1976) have been proposed by early reviewers of the topic, but no data or controlled studies were being quoted to support the validity of these medical observations. Indeed, khat chewers may suffer inflammatory and traumatic lesions of the oral mucosa.…”
Section: Buccal Cavity and Digestive Systemmentioning
confidence: 95%